2018
DOI: 10.1097/prs.0000000000004976
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Bone Remodeling and the Clockwise Rotation of the Facial Skeleton: A Computed Tomographic Imaging–Based Evaluation

Abstract: acial aging is a multifactorial process involving different facial tissues: bone, ligaments, muscles, fat, and skin. The onset and the pace of age-related changes of each tissue type or structure vary between different individuals, genders, and ethnic backgrounds. The different facial bones provide the foundation for all overlying structures, and several previous studies have identified the importance of their age-related changes when trying to evaluate and treat the signs of facial aging. 1-13 Pessa, 2 using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…Signs of facial aging include volume loss and soft tissue sagging. These phenomena are interrelated and can be attributed to the continuous facial aging process affecting bone, ligaments, muscles, fat, and skin . Recent studies have shown that over time fat is redistributed from subcutaneous locations such as the superficial and deep facial fat compartments to intra‐abdominal or ectopic locations such as the liver or the bone marrow .…”
Section: Introductionmentioning
confidence: 99%
“…Signs of facial aging include volume loss and soft tissue sagging. These phenomena are interrelated and can be attributed to the continuous facial aging process affecting bone, ligaments, muscles, fat, and skin . Recent studies have shown that over time fat is redistributed from subcutaneous locations such as the superficial and deep facial fat compartments to intra‐abdominal or ectopic locations such as the liver or the bone marrow .…”
Section: Introductionmentioning
confidence: 99%
“…It could be speculated that in males, a greater effect could be expected as the muscular response might be larger resulting a greater volume increase of the temporal fossa. On the other side, it can be speculated that age might result in a limited effect of temporal volumization, as with increasing age the soft tissue of the temple additionally contributes to temporal hollowing 13‐17 . Future clinical trials should account for various gender‐ and age‐related factors to best elaborate on the results and discussions presented herein.…”
Section: Discussionmentioning
confidence: 92%
“…On the other side, it can be speculated that age might result in a limited effect of temporal volumization, as with increasing age the soft tissue of the temple additionally contributes to temporal hollowing. [13][14][15][16][17] Future clinical trials should account for various gender-and age-related factors to best elaborate on the results and discussions presented herein.…”
Section: Temporal Volume Scalementioning
confidence: 99%
“…Facial aging is a multifactorial process involving all tissues of the face: bones, muscles, ligaments, fat, and skin. [1][2][3][4][5] Despite the fact that each tissue ages at its own pace and starts at a different time point, the visible signs of facial aging can be observed in each individual. 6 Soft tissue descent, facial volume loss, and alterations in skin texture and color are the main reasons why patients seek esthetic advice and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…esthetic effects, facial anatomy, fascial layers, safety, soft tissue fillers, temple is due to the anthropometric differences between a male and female skull. [2][3][4] In general, the temporal region extends between the zygomatic arch (inferior) and the temporal crest (superior) and between the lateral orbital margin (anterior) and the occipital boundary of the temporalis muscle which is 1-3 cm posterior to a vertical line passing through the external auditory meatus (posterior). The posterior boundary of the temple is of less clinical importance as it is covered by hair.…”
Section: Introductionmentioning
confidence: 99%